37. EVALUATION OF THE EFFECTIVENESS OF MIDAZOLAM COMBINED WITH DEXAMETHASONE IN PREVENTING NAUSEA AND VOMITING AFTER SPINAL ANESTHESIA FOR CESAREAN SECTION (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate and compare the efficacy of Midazolam combined with Dexamethasone versus Dexamethasone alone in preventing postoperative nausea and vomiting in parturients undergoing cesarean section under spinal anesthesia.Object and methods: A randomized, controlled, single-blind clinical trial with a parallel-group design was conducted on 80 parturients undergoing elective cesarean section under spinal anesthesia at Thai Nguyen National Hospital from April 2025 to July 2025. Participants were randomly assigned to two groups: group D received 8 mg of intravenous Dexamethasone immediately before spinal anesthesia; group MD received 8 mg of intravenous Dexamethasone immediately before spinal anesthesia and 0.03 mg/kg of intravenous Midazolam immediately after umbilical cord clamping.Results: The incidence of postoperative nausea was significantly higher in group D (20%) compared to group MD (7.5%) (p < 0.05). Postoperative nausea and vomiting within the first 6 hours postoperatively was also significantly more frequent in group D (37.5%) compared to group MD (12,5%). Furthermore, the severity of postoperative nausea and vomiting, assessed using the Klockgether-Radke scale, was significantly lower in group MD across all time points.Conclusion: The combination of Midazolam and Dexamethasone significantly reduces the incidence and severity of postoperative nausea and vomiting following cesarean section under spinal anesthesia, particularly within the first 6 hours postoperatively.
Keywords: Dexamethasone, Midazolam, spinal anesthesia, cesarean section, postoperative nausea and vomiting.